RAD MODEL TO DESIGN AND CONSTRUCT FISH FEEDING EQUIPMENT IN NEGERI SAKTI PESAWARAN AUTOMATICALLY AND EFFICIENTLY - Bachry, Bobby; Rifa'i, Rendra Nasrul; Kesuma, Mezan El-Khaeri; Yudiansyah, Lepi Astra (Bakti Nusantara Institute, 2024)
This research paper explores the design and construction of an automated fish feeder in the village of Negeri Sakti Pesawaran, aimed at enhancing efficiency in fish feeding, reducing errors, and boosting productivity and sustainability in fish farming. The study adopts the Rapid Application Development (RAD) method for its quick and iterative development approach. The methodology involves identifying needs, forming a development team, project planning, prototyping, system construction, and functionality testing. The implementation of the automated feeder has shown positive impacts on fish farming in Pesawaran. Challenges encountered during development have provided opportunities for learning and improvement. The success of this project serves as a foundation for the advancement of similar technologies in the aquaculture sector.